A decision support model for the operational management of employee redeployment in large governmental organisations. (18th August 2020) - Hajnić, Miljenko; Mileva Boshkoska, Biljana
ABSTRACT: The rapid and appropriate redeployment of employees among workplaces is a common task for companies that consist of many organizational units geographically distributed across the country. The redeployment requires matching of the employee's education, skills and competences to the work unit requirements. In this paper, we present a decision support model for employee redeployment and selection of the best candidate for a given position in a large governmental organisation geographically distributed in many organisational units throughout the country. The proposed decision support model can be used in general or may be adapted to fit the organizational needs and the configuration of the specific conditions of the different organisational units. Once defined, the decision support model aids the decision-maker in the process of candidates' evaluations for the selected working places that significantly accelerate the selection process of candidates for redeployment.